2009
DOI: 10.1080/10549810903344660
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Selected Genotype ofAloe veraL.—An Ancient Plant for Modern Industry

Abstract: Aloe vera Linn. (Syn. Aloe barbadensis Mill; Gwar-patha in Hindi) belongs to family Liliaceae. The plant, for its medicinal properties, has commercial value. Some of the genotypes of Aloe vera are consumed as a vegetable and processed to make curry and other edible products. We report here on the development of an efficient method for rapid clonal propagation by shoot proliferation from axillary meristem (s) of selected germplasm of Aloe vera. Explants were pretreated with 0.1% aqueous solution of both strep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 24 publications
5
19
0
1
Order By: Relevance
“…Reducing the level of 2,4-D in culture medium and raising osmotic concentration of the medium could reduce the hyper-hydration of cultures. It is also suggested that once meristematic activity is achieved then cultures could be maintained or grown on medium containing lower concentration of plant growth regulators [12]. Therefore cultures were transferred on MS medium containing lower concentration (1.5 mg l −1 ) of 2,4-D along with 0.25 mg l −1 of Kin, 4% carbohydrate source (3.0% sucrose and 0.5% each of maltose and glucose), and additives for multiplication and long-term maintenance of regenerative callus cultures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing the level of 2,4-D in culture medium and raising osmotic concentration of the medium could reduce the hyper-hydration of cultures. It is also suggested that once meristematic activity is achieved then cultures could be maintained or grown on medium containing lower concentration of plant growth regulators [12]. Therefore cultures were transferred on MS medium containing lower concentration (1.5 mg l −1 ) of 2,4-D along with 0.25 mg l −1 of Kin, 4% carbohydrate source (3.0% sucrose and 0.5% each of maltose and glucose), and additives for multiplication and long-term maintenance of regenerative callus cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Bairu et al [11] incorporated meta-topolin [6-(3-hydroxybenzylamino) purine] and its derivatives as alternatives to the benzyladenine and zeatin for optimizing the micropropagation protocol for A. polyphylla. Singh et al [12] defined micropropagation system for mass propagation of selected genotypes of A. vera using axillary meristems. Reports on plant regeneration via callus or somatic embryogenesis of A. vera are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is suggested that once tissue become rejuvenated and regeneration potential is achieved with cytokinins treatments, the tissue become conditioned and thus require a low level of cytokinins for further proliferation. Hyper-hydration could be checked by reducing the level of cytokinins and raising the osmotic concentrations of culture medium (Singh et al, 2009). In the present study significantly elongated and viable micro-shoots were obtained on MS medium with low level (1.11 μM) of BAP.…”
Section: Discussionmentioning
confidence: 99%
“…Vyas University, Jodhpur served as source of explants. Efficient plantlet regeneration both through direct shoot bud proliferation without callus phase (protocol 1) using axillary shoot buds [10] and indirect shoot bud proliferation via intermediate callus phase (protocol 2) using soft base of inflorescence axis as an explant [11] was achieved. Figure 1 shows a schematic representation of different steps of protocols and Murashige and Skoog's basal medium [22] with plant growth regulators used for plantlet regeneration.…”
Section: Methodsmentioning
confidence: 99%
“…Efficient plantlet regeneration for a selected genotype of A. vera L. sweet aloe was achieved through direct shoot bud proliferation using axillary shoot buds [10] and indirect shoot bud regeneration via an intervening callus phase using inflorescence axis as explants [11]. Plant tissue culture techniques are of extensive uses where quality material of a selected genotype is required at mass scale, for commercial cultivation and the natural propagation do not meet the required demands.…”
Section: Introductionmentioning
confidence: 99%